Alpi : the soul sender. 3 - Rona (Manga artist) (Titan Comics, 2024)
Alpi must look death square in the face as she conducts a funeral for the people of a lonely fortress. The young girl needs to muster her courage to face down both the spirits of the world and the next life beyond in the all-new volume of Alpi the Soul Sender!